Intersex and liver alterations induced by long-term sublethal exposure to 17α-ethinylestradiol in adult male Cnesterodon decemmaculatus (Pisces: Poeciliidae) - Young, Brian Jonathan; López, Gabriela Carina; Cristos, Diego Sebastian; Crespo, Diana Elvira; Somoza, Gustavo Manuel; Carriquiriborde, Pedro (2017)
The aim of the present study was to assess the responses of the gonopodium morphology and the gonadal and liver histology of adult male Cnesterodon decemmaculatus to sublethal long-term exposure concentrations of 17a-ethinylestradiol (EE2). Two experiments were conducted exposing the fish to waterborne concentrations of EE2 ranging from 20 ng/L to 200 ng/L for 8 wk, 12 wk, and 16 wk. Intersex gonads were observed after 8wk and 16 wk in fish exposed to 200 ng EE2/L and 100 ng EE2/L, respectively. Oocytes’ development from testis germ cells and replacement of the efferent duct periodic acid-Schiff–positive secretion surrounding spermatozeugmata by parenchymal tissue and duct structure alterations were the major observed changes in the gonads. In contrast, no response was observed in the gonopodium morphology. Liver histology was also altered, showing increasing steatosis, single-cell necrosis to generalized necrosis, and disruption of acinar organization from 100 ng EE2/L to 200 ng EE2/L. In summary, the present results showed that although EE2 was not able to alter the morphology of a developed gonopodium, it was capable of inducing development of testicular oocytes in adult male C. decemmaculatus at environmentally relevant concentrations. Thus, externally normal but intersex C. decemmaculatus males would be expected in the wastewater-receiving streams that the species inhabits. According to the literature, the present study would be the first indicating estrogen-induced intersex in adult male poeciliid.